FASHION AND GENDER EQUALITY - Tendulkar, Prachi; Goyal , Pratima (International Journal of Research -GRANTHAALAYAH, 2025)
In recent years, fashion has emerged as a pivotal arena for advancing gender equality globally. The research investigates the complex and interesting interplay between fashion and gender equality, focusing theoretically on social constructionist perspectives to explain how fashion reflects and shapes societal norms and gender identities. The objective is to examine the perception of people towards the fashion industry contributing to the discourse and advancement of gender equality through its representations and impact on societal attitudes. Drawing on social constructionist theories, the findings explore how fashion constructs and perpetuates gender norms, as well as how it can challenge and redefine these norms through design, marketing, and activism. A mixed-methods approach is also utilized, combining qualitative analysis of runway shows, and quantitative analysis of societal attitudes towards gender and fashion trends. Data collection involves content analysis of fashion media and surveys assessing public perceptions. This anticipates findings that demonstrate fashion’s significant role in shaping and reflecting societal attitudes toward gender. It expects to uncover examples where fashion initiatives have led to tangible shifts in perceptions and policies related to gender equality. The result also contributes to provide empirical evidence and theoretical insights into how fashion can catalyze gender equality. By understanding the mechanisms through which fashion influences gender norms and perceptions, the research aims to inform both industry practices and societal discourse, fostering more inclusive and equitable representations within the fashion landscape. Ultimately, the aim is to underscore the transformative potential of fashion in advancing gender equality, highlighting avenues for future research and actionable strategies to leverage fashion’s influence on social change.